Synthesis and Characterization of Bis-Dithiocarbamate Disubstituted Derivative of Calix[4]arene as a New Macrocyclic Ligand for Construction of Ion Selective Electrode - Jahanshahi-Anboohi, Fatemeh; Rezaie, Gisa (Asian Journal of Chemistry, 2012)
In this communication, the synthesis and structure determining of 5,11,17,23-tetrakis(2,2,3,3- tetra methyl butyl)-25,27-bis(N,N diethyldithio carbamoyl propoxy)-26,28-dihydroxy calix[4]arene, which has selective complexing behaviour has been reported. According to substitutability at lower rim of calix[4]arene it can be possible to selective connecting of diethyl dithiocarbamate units at this position. The existence of calix[4]arene units in obtained molecule cause selective behaviour of dithiocarbamoyl part, so complexes are formed, which have special ion selective characteristics and are used in constructing of ion selective electrodes and electrochemical sensors. The structural properties and characteristics of obtained molecule are determined by different spectroscopic methods.